Fading Spectrophotometric Determination of Pioglitazone Hydrochloride with Eosine B - Ma, Wei-Xing; Li, Na; Sha, Ou; Liu, Ying-Hong (Asian Journal of Chemistry, 2012)
A fading spectrophotometric method for the determination of pioglitazone hydrochloride was carried out based on the reaction between pioglitazone hydrochloride and eosine B to form ion-association complex with the fading absorption peak at 518 nm, where the absorbance DA was correlated with its concentration. Linear relationship with good correlation coefficient (0.9996) was found between the absorbance DA and the concentration of pioglitazone hydrochloride in a concentration range of 3-27 μg mL-1. The proposed method was successfully applied to the determination of the investigated drug in tablets or capsules in agreement with the results of ultraviolet spectrophotometry.